2011
DOI: 10.14704/nq.2011.9.4.486
|View full text |Cite
|
Sign up to set email alerts
|

Altered States of Consciousness Occurring During Expanded Sexual Response In The Human Female: Preliminary Definitions

Abstract: Expanded Sexual Response (ESR) is a recently defined phenomenon. It is defined as "being able to attain long lasting and/or prolonged and/or multiple and/or sustained orgasms and/or status orgasmus that lasted longer and more intense than the classical orgasm patterns defined in the literature". During our detailed preliminary survey to investigate the claimed ESR phenomenon in some particular women, we also investigated the subjective feelings and altered states of consciousness (ASC) during very intense and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
0
13
0
4
Order By: Relevance
“…During the Dionysus rituals, Bacchae danced, joined the entertaining people, and served wine and psychoactive drinks, such as kykeon or absinthe. Most of the Bacchae were insatiable and hypersexual-hyper orgasmic ESR women who joined the dances of the festival, as well as the long lasting sexual activities of the Dionysus Cult (Sayin, 2011(Sayin, , 2012a(Sayin, , 2012b(Sayin, , 2014Euripides, B.C. ;Azar, 2006;Daniélou, 1992;Ruck, 2000Ruck, , 2001Ruck, , 2006aRuck, -b, 2013.…”
Section: Bacchaementioning
confidence: 99%
“…During the Dionysus rituals, Bacchae danced, joined the entertaining people, and served wine and psychoactive drinks, such as kykeon or absinthe. Most of the Bacchae were insatiable and hypersexual-hyper orgasmic ESR women who joined the dances of the festival, as well as the long lasting sexual activities of the Dionysus Cult (Sayin, 2011(Sayin, , 2012a(Sayin, , 2012b(Sayin, , 2014Euripides, B.C. ;Azar, 2006;Daniélou, 1992;Ruck, 2000Ruck, , 2001Ruck, , 2006aRuck, -b, 2013.…”
Section: Bacchaementioning
confidence: 99%
“…Prolonged meditation, sensory deprivation, hypnosis can induce similar consciousness states without the intake of any chemicals (Austin, 1999;Tart, 1990;Lilly, 1972). In some women, expanded sexual response (ESR) and expanded orgasms (EO) may mimic the acute effects of some hallucinogens for a very short period of time (Sayin, 2011;Taylor, 2000;. For centuries, mystical experiences through yoga, Zen meditation, prayers have been cited to induce a kind of ASC (Muramuto, 2004;Wain 2007;Austin, 1999;Tart, 1990).…”
Section: Question 1: How Can We Explain Tens Of Different Perception mentioning
confidence: 99%
“…It has been proposed that altered states of consciousness can be attained through various methods, such as Zen meditation (Austin, 1999), expanded sexual response (ESR) (Sayin, 2011;Taylor, 2000;, hypnosis (Ross, 2006;Tart, 1990;Ludwig, 1965 ), metabolic changes (Hobson, 1994;Tart, 1990;), sensory deprivation (Lilly, 1972;Tart, 1990), hallucinogenic drugs (Brunton, 2010;Hardman, 2001;Shulgin, 1991;Tart, 1990;Grof, 1985;Goodman, 1980;Stafford, 1978;Brimblecombe, 1973), central nervous system (CNS) stimulants (Rothman, 2001;Hobson, 1994;Tart, 1990;Nielsen, 1988 ), physiological sleep (Hobson, 1988;Tart, 1990), anesthetic drugs (PCP, Ketamine) (Tart, 1990;Stafford, 1978), etc. Although involvement of many receptor and neurotransmitter systems have been proposed in the mechanism of action of H-ASC inducing drugs, there has been no consensus on the basic mechanisms of some particular effects of some hallucinogenic drugs, such as LSD, ibogaine, THC (tetrahydrocannabinol), PCP (phencyclidine), MDMA, methamphetamine, mescaline, psilocybin, DMT and many others.…”
mentioning
confidence: 99%
“…Recently, other intra-vaginal erogenous zones have been proposed to be discovered that may take part in the mechanisms of female orgasms (Morris, 2004;Sayin 2012 a-b-c). Also Komisaruk et al and Sayin et al (Komisaruk, 2006;Sayin, 2010Sayin, , 2011Sayin, a-b-c, 2012 have reported that female orgasm can be triggered by means of the stimulation of other erogenous zones via different neural pathways, while "the brain" and the psychology of the woman played the major role. According to the novel accumulating data, glans clitoris was responsible of the 'clitoral orgasms' via a reflex pathway originating from pudental nerve and sacral plexus, while other vaginal erogenous zones, coined as "deep vaginal erogenous zones" (DVZ) were responsible of 'vaginal orgasms', via other orgasm reflex pathways, such as pelvic nerve-sacral plexus, hypogastric nerve-pelvic plexus and vagus nerve-brain (Ladas, 1982;Komisaruk, 2003Komisaruk, , 2004Komisaruk, , 2005Komisaruk, , 2006Sayin, 2010Sayin, , 2011aSayin, -b-c, 2012aSayin, -b-c, 2013.…”
mentioning
confidence: 99%
“…Also the term of "blended orgasm" had been defined by Ladas et al (Ladas, 1983) and Sayin et al (Sayin, 1993, 2010, 2011c, 2012a. "Four nerve theory of female orgasmic response" was hypothesized to explain the mechanisms of single, multiple and extreme prolonged orgasms or ESR in the human female (Komisaruk, 2006;Sayin, 2011Sayin, a-b, 2013). …”
mentioning
confidence: 99%